Presidential Election Confirms France’s Divide - Helmut Reisen (Wirtschaftsdienst)
Abstract French presidential elections 2022 have significantly strengthened anti-EU populists. Traditional mainstream centrists are not among the big three election winners, while far-right Marine Le Pen deftly addressed the plight of the disengaged. The country’s rural-urban divide masks significant differences in voting motives; Paris is a stark outlier. Unemployment rates, low skills, and car dependency fuel Le Pen’s support, as well as xenophobia. The province has fought back against neglect by electing populists. It is doubtful whether place-based policies will solve the structural cause of the populist tendency by the next presidential election in five years.